A Suitable procedure for preparing of water Samples used in Radiocarbon Intercomparison. Issue 6 (24th September 2019) - Takahashi, H A; Minami, M; Aramaki, T; Handa, H; Saito-Kokubu, Y; Itoh, S; Kumamoto, Y
ABSTRACT: We studied a suitable procedure for preparing of water samples used in radiocarbon intercomparisons involving dissolved inorganic carbon (DIC). The water samples must have inter-batch consistency and stable 14 C concentrations and no sterilizing agent (e.g., HgCl2 ) should be added, in order to avoid the production of hazardous material. Six water samples, containing widely different amounts and types of salts, DIC, and 14 C concentrations (1–100 pMC), were prepared in order to assess the procedure. Sample consistency was investigated through δ 13 C and chemical compositions; their low variabilities indicate that our procedure can be applied to radiocarbon intercomparison. A specific sample preparation protocol was developed for this kind of applications.